Hantavirus: an overview and advancements in therapeutic approaches for infection - Afzal, Samia; Ali, Liaqat; Batool, Anum; Afzal, Momina; Kanwal, Nida; Hassan, Muhammad; Safdar, Muhammad; Ahmad, Atif; Yang, Jing (Frontiers in Microbiology, 2023)
Hantaviruses are a significant and emerging global public health threat, impacting more than 200,000 individuals worldwide each year. The single-stranded RNA viruses belong to the Hantaviridae family and are responsible for causing two acute febrile diseases in humans: Hantavirus pulmonary syndrome (HPS) and hemorrhagic fever with renal syndrome (HFRS). Currently, there are no licensed treatments or vaccines available globally for HTNV infection. Various candidate drugs have shown efficacy in increasing survival rates during the early stages of HTNV infection. Some of these drugs include lactoferrin, ribavirin, ETAR, favipiravir and vandetanib. Immunotherapy utilizing neutralizing antibodies (NAbs) generated from hantavirus convalescent patients show efficacy against HTNV. Monoclonal antibodies such as MIB22 and JL16 have demonstrated effectiveness in protecting against HTNV infection. The development of vaccines and antivirals, used independently and/or in combination, is critical for elucidating hantaviral infections and the impact on public health. RNA interference (RNAi) arised as an emerging antiviral therapy, is a highly specific degrades RNA, with post-transcriptional mechanism using eukaryotic cells platform. That has demonstrated efficacy against a wide range of viruses, both in vitro and in vivo. Recent antiviral methods involve using small interfering RNA (siRNA) and other, immune-based therapies to target specific gene segments (S, M, or L) of the hantavirus. This therapeutic approach enhances viral RNA clearance through the RNA interference process in Vero E6 cells or human lung microvascular endothelial cells. However, the use of siRNAs faces challenges due to their low biological stability and limited in vivo targeting ability. Despite their successful inhibition of hantavirus replication in host cells, their antiviral efficacy may be hindered. In the current review, we focus on advances in therapeutic strategies, as antiviral medications, immune-based therapies and vaccine candidates aimed at enhancing the body's ability to control the progression of Hantavirus infections, with the potential to reduce the risk of severe disease.